Probabilistic approach to assess URM walls with openings using discrete rigid block analysis (D-RBA). (1st December 2022) - Pulatsu, Bora; Gonen, Semih; Parisi, Fulvio; Erdogmus, Ece; Tuncay, Kagan; Funari, Marco Francesco; Lourenço, Paulo B.
Abstract: This study aims to improve our current understanding of the seismic assessment of load-bearing unreinforced masonry (URM) systems by proposing a probabilistic computational modeling framework using the discrete element method (DEM). The main objective is to predict the structural behavior and capacity of URM walls with openings subjected to lateral loading, considering uncertainties in material properties. The proposed modeling strategy represents masonry as an assembly of rigid blocks interacting along their boundaries by adopting the point-contact hypothesis. Fracture energy-based softening contact models are implemented into a commercial discrete element code (3DEC) to better simulate both the pre- and post-peak behavior of masonry. The results highlight the influence of material properties on the force capacity, displacement capacity (drift limits), and collapse mechanisms of walls with openings. Based on the applied non-spatial probabilistic analyses, the most commonly observed failure mechanisms are further assessed using a simplified macro-block formulation. As a result, practical, yet necessary, inferences are made, providing valuable contributions. Furthermore, the validated discontinuum analysis framework is demonstrated as an accurate structural analysis strategy and a useful approach to simulating the potential collapse mechanism of load-bearing URM structures. Highlights: A probabilistic computational modeling framework is adopted to assess URM walls with openings. Uncertainty in material properties is taken into consideration in the computational models. The most and least commonly observed failure mechanisms and their force-displacement capacities are discussed. The detrimental influence of weak-pier and strong-spandrel systems is highlighted. A practical macro-block analysis is presented, relying on the pre-defined crack patterns obtained from advanced solutions.